Resolución de problemas de Química y estructura cognoscitiva - Kempa, R. F. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2007)
This paper introduces a research about the causes of students incapability to solve successfully questions typical from chemistry testing. The relationship between cognitive maps of good and poor solvers and their answers is studied. The results obteined when studying the influence of the level of information supplied by the declaration of a problem over its level of facility is offered.